1981
DOI: 10.1002/cne.902030308
|View full text |Cite
|
Sign up to set email alerts
|

Aging in the rat olfactory system: Correlation of changes in the olfactory epithelium and olfactory bulb

Abstract: Two regions closely linked synaptically (olfactory epithelium and olfactory bulb) have been compared in an age-graded series of rats. Previous findings of growth and atrophy of constituent elements in Sprague-Dawley Wisconsin (SD) rats have now been confirmed in Charles River (Crl) rats. In the olfactory bulbs of Charles River (Crl) rats, the volume of layers, the number of olfactory axodendritic synapses in the glomeruli, the total volume of glomerular dendrites, and the size of mitral cell bodies all approxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
85
2

Year Published

1995
1995
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(104 citation statements)
references
References 22 publications
17
85
2
Order By: Relevance
“…Contrary to earlier reports of extensive volume and cell losses in the aging brain, our data suggest more subtle region-and layer-specific changes (1, 2). In the OB, there are reports of both strain-and species-dependent effects of aging (14)(15)(16)(17). Our results, which included more intermediate time points, establish that OB volume is stable from 2 mo onward in C57BL/6J mice.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Contrary to earlier reports of extensive volume and cell losses in the aging brain, our data suggest more subtle region-and layer-specific changes (1, 2). In the OB, there are reports of both strain-and species-dependent effects of aging (14)(15)(16)(17). Our results, which included more intermediate time points, establish that OB volume is stable from 2 mo onward in C57BL/6J mice.…”
Section: Discussionsupporting
confidence: 71%
“…The significant loss of glomerular A:D synapses we report here is likely related to global reductions in OSN density and OR-specific OSN subpopulations (4,14,(18)(19)(20). In contrast, D:D synapses are also lost despite stability of the number of PG and mitral/tufted cells.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Anatomical changes associated with aging have been detected in both peripheral olfactory structures, e.g., olfactory epithelium (Naessen, 1971;Dodson and Bannister, 1980), and central olfactory pathways, e.g., olfactory bulb (Liss and Gomez, 1958;Hinds and McNelly, 1981), but their relative contributions to the age-related functional deficits are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The present study also demonstrated difference in the shape of dendrites extending from perikarya located at various heights of the epithelium. The following reasons are possible explanations for this phenomenon: 1) Olfactory receptor cells are known to be continuously renewed [8,29]. Since newly differentiated cells have to extend their dendrite to the surface of epithelium through a densely packed cell mass, the extension of dendrite may be mechanically affected, resulting in thin and winding dendrites.…”
Section: Morphology Of Olfactory Receptor Cells: the Detailedmentioning
confidence: 99%